Our experience on Actovegin, is it cutting edge? - Lee, P.; Rattenberry, A.; Connelly, S.; Nokes, L. (International Journal of Sports Medicine, 2011)
Muscle injuries are one of the most common sport related injuries, their incidence varying from 30-55% in all sports injuries. They account for the loss of 90 training days and 15 matches per club per season in elite football (soccer). In recent years, the use of Actovegin® in sports medicine has caused a lot of controversy in many sports disciplines. Although it is unlikely for this deproteinised substance to have oxygen-enhancing capacity, there is an anecdotal belief that Actovegin® can increase an athlete's performance. Actovegin® is produced by Nycomed Austria GmbH and has been used by doctors across Europe, China and Russia for over 60 years. Nevertheless, very little is known regarding the effects of Actovegin on muscle injuries. This article reviews the current evidence on Actovegin®, its legal status with sports governing bodies and its potential role in sport injuries. We will also report our experience with this drug in treating muscle injuries. In this pilot study, players in the Actovegin treatment group were able to return to play 8 days earlier (95% CI -1.249 to -14.7510) compared to physiotherapy alone (p=0.033). No adverse reactions were recorded in any of the participants.